2019
DOI: 10.1371/journal.pone.0212998
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a common mechanism of spatial attention and visual awareness: Towards construct validity of pseudoneglect

Abstract: Present knowledge of attention and awareness centres on deficits in patients with right brain damage who show severe forms of inattention to the left, called spatial neglect. Yet the functions that are lost in neglect are poorly understood. In healthy people, they might produce “pseudoneglect”—subtle biases to the left found in various tests that could complement the leftward deficits in neglect. But pseudoneglect measures are poorly correlated. Thus, it is unclear whether they reflect anything but distinct su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…We expect faster left dot detection to be attenuated under high attentional load but this predicted attenuation may (or may not) be modulated further by age. A similar attempt in this direction has been made in a very recent study by Chen et al [51] who reported that adding visual noise to landmark, greyscale and gratingscales tasks increased left spatial bias in young adults. Further neuroimaging studies should also be undertaken to characterize such possible modulators of pseudoneglect.…”
Section: Discussionmentioning
confidence: 61%
“…We expect faster left dot detection to be attenuated under high attentional load but this predicted attenuation may (or may not) be modulated further by age. A similar attempt in this direction has been made in a very recent study by Chen et al [51] who reported that adding visual noise to landmark, greyscale and gratingscales tasks increased left spatial bias in young adults. Further neuroimaging studies should also be undertaken to characterize such possible modulators of pseudoneglect.…”
Section: Discussionmentioning
confidence: 61%
“…Nonetheless, this trend is likely the first physiological sign appearing when leftward spatial bias begins to falter in the early neurodegenerative condition. We speculate that while healthy participants have a functionally preserved inferior parietal lobule where the visual information is quickly integrated across hemispheres to form a leftward-biased topography of the input ( Le et al, 2015 ; Chen et al, 2019 ), the initial degeneration of transcallosal connections in patients with aMCI may have contributed to affect this early parietal advantage when enumerating small quantities. Conversely, when enumerating larger quantities, some aspects of the evidence accumulation process may have preserved pseudoneglect in patients with aMCI.…”
Section: Discussionmentioning
confidence: 99%
“…They also differ in their cognitive processing demands with one task being a simple detection task and the other task requiring a judgment on spatial properties. However, the degree to which different tasks tap into different underlying spatial mechanisms is a matter of debate 45 and our study was not designed to disentangle these mechanisms. Also, a recent meta-analysis did not find evidence that effect sizes for associations between alertness and spatial attention differ between tasks requiring speeded responses to stimuli (i.e., detection of stimuli) and judgement tasks such as the Landmark Task 17 .…”
Section: Discussionmentioning
confidence: 99%